PENINGKATAN PENGETAHUAN ANAK TENTANG KESEHATAN GIGI DAN MULUT MENGGUNAKAN MEDIA VIDEO ANIMASI - Elsi Rahmadani; Siti Zulva; Melani Sri Cahyani; Yunisa Putri Damayani; Lesa Aprina Putri (Stikes Syedza Saintika Padang, 2026)
School-aged children, especially elementary school children, are vulnerable to dental and oral health problems, especially dental caries and cavities, and other oral problems. This is based on a lack of knowledge about the importance of dental and oral care. Animated video media is an educational tool that can be heard and seen, can help students in the teaching and learning process, and serves to clarify or facilitate understanding of the language being studied. This study aims to improve dental and oral knowledge using animated video media. This type of research is an experiment using a pretest and posttest group design on fourth-grade students at SDN X Bengkulu. Sampling was done by random sampling. The sample in this study was 33 fourth-grade students of SDN X Bengkulu. The data analysis technique used the Wilcoxon Sign Rank Test. The results of the study showed that there was an educational effect on knowledge about teeth and mouth using animated video media. The conclusion is that there was an educational effect on knowledge about teeth and mouth using animated video media at SDN Bengkulu. Keywords: Knowledge, Animated Video, Dental and Oral Health